Changes in the proportions of two mitochondrial populations during the development of embryonic chick liver - Pollak, J. K. (1971)
1. Two populations of morphologically intact mitochondria were isolated from embryonic, neonatal and adult chick liver by isopycnic centrifugation. 2. The protein/phospholipid ratio of the total mitochondrial fraction, the low-density mitochondria (B2, d1.176) and the high-density mitochondria (B3, d1.206) did not differ significantly. 3. During development there is a marked increase in the B2 fraction in relation to the B3 fraction. 4. Cytochrome oxidase and malate dehydrogenase activities as well as respiratory control increased during the embryonic development of the chick, though their rates of increase were not correlated. 5. In the three different embryonic stages that were investigated, as well as in the neonatal and adult chick, the protein/lipid as well as the protein/phospholipid ratio stayed constant and showed no progressive increase, as had been previously reported. 6. It was shown that forces greater than 18400g(av.) for 2h have to be used before chick liver mitochondria reach isopycnic equilibrium. 7. As for rat liver mitochondria, the constant protein/phospholipid ratio of the B2 and B3 fractions and their apparent morphological intactness leads one to conclude that the matrix space of B2 mitochondria is inaccessible to sucrose, whereas B3 mitochondria possess an inner membrane that is permeable to sucrose.